The Effect Of Human Resource Development On Employee Performance Through Training At The Regional Inspectorate Office Binjai City - Septy Wanna Masayu; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
Human Resource Development (HR) has a strategic role in improving employee training and performance. This study aims to analyze the influence of human resource development on employee performance with training as an intervening variable at the Binjai City Regional Inspectorate Office. This study uses an associative quantitative method with a causal approach, involving 68 respondents who are employees in the office. The data was analyzed using the Partial Least Squares (PLS) method to measure the direct and indirect influence between the research variables. The results of the study showed that human resource development had a positive and significant effect on training with a T-Statistic value of 27.607 > 1.96 and a P-Value of 0.000 < 0.05. In addition, human resource development also has a significant direct influence on employee performance, as evidenced by the T-Statistic value of 5.788 > 1.96 and the P-Value of 0.000 < 0.05. The training proved to have a significant effect on employee performance with a T-Statistic value of 3.269 > 1.96 and a P-Value of 0.002 < 0.05. The indirect influence shows that the training is able to intervene the relationship between human resource development and employee performance, with a T-Statistic value of 3.139 > 1.96 and a P-Value of 0.003 < 0.05. The implications of this study emphasize the importance of effective human resource development policies, not only in the form of salaries and benefits, but also structured training. This policy, accompanied by a supportive work environment, will create a synergistic effect in increasing employee productivity and loyalty.